Timing of Proactive Organizational Consulting: Difference between Organizational Perception and Behaviour - Ichak Adizes; Mladen Cudanov; Dusanka Rodic (Amfiteatru Economic Journal, 2017)
The aim of this paper is to show organizational perceptions and behaviours regarding proactive search for consultancy services. Management consulting is operating primarily through the analysis of perceived and existing organizational problems, but on the other hand it could be considered as a creation of value for organizations through the application of knowledge, techniques and, assets to improve organizational performance which is in the unknown and hidden potential part of organizational Johari window. Perceptions of organization are shown through managers and consultants perceptions survey in southeast Europe region. From the other side as an empirical base of real managerial behaviours there is a database of companies which had been proactively asking for consultancy services in southeast Europe region. This research is based on Adizes Institute database, which is the reason we have introduced the Adizes Corporate Lifecycle model theory. We will show the difference of perceptions at what stage in lifecycle organizations should engage consultant help and reality, when companies actually do that. We will use data analysis results to discuss whether timing when organizations decide to proactively engage consultants is the right time for such engagement.
Keywords: L29; L84; M10; 330; Management consulting; Adizes Corporate Lifecycle stages; managerial perceptions; organizational reality; Johari window in organizational consultancy context